1987
DOI: 10.1002/clc.4960100815
|View full text |Cite
|
Sign up to set email alerts
|

Acute aortic regurgitation due to spontaneous rupture of a bicuspid aortic valve: Detection by echocardiography

Abstract: Summary:A 42-year-old man was admitted with acute severe aortic regurgitation. There were no signs of a systemic infection. M-mode and two-dimensional echocadiography revealed bicuspid aortic valve and echocardiographic features consistent with aortic leaflet rupture. The diagnosis was confirmed at surgery. This report illustrates that spontaneous rupture of a bicuspid aortic valve should be considered in acute aortic regurgitation without infective endocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Acute aortic valve regurgitation due to spontaneous rupture of a BAV is very rare. The first case report was published by Ciampricotti et al in 1987 [3] . To our knowledge, this is the first published report of spontaneous rupture of a BAV after heavy weightlifting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute aortic valve regurgitation due to spontaneous rupture of a BAV is very rare. The first case report was published by Ciampricotti et al in 1987 [3] . To our knowledge, this is the first published report of spontaneous rupture of a BAV after heavy weightlifting.…”
Section: Discussionmentioning
confidence: 99%
“…He had not previously had a TTE, and had undergone only one routine ECG from his general practitioner, without any abnormal findings. The possibility of developing high blood pressure during his exhaustive training combined with the weakened aortic valve structure, could have led to the spontaneous rupture since no calcifications were found [3,4] . Interestingly, it was recently reported that heavy calcific deposits in BAV may extend across the orifice causing a perforation in the noncalcified portion of the opposing cusp [5] .…”
Section: Discussionmentioning
confidence: 99%